2020
DOI: 10.20414/betajtm.v13i2.380
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the effects of problem-based learning on students' creative thinking in mathematics

Abstract: [English]: This study examined the effect of Problem-based Learning (PBL) on students' creative mathematical thinking in Indonesia during the last eight years using meta-analysis. Data were obtained from primary studies published in national journals, conference proceedings, and master thesis from 2012 to 2020. This study analyzed 19 effect sizes from 19 primary studies that fulfill the inclusion criteria. The effect size index used the Hedges' g equation and statistical analysis was assisted by comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
5
13
0
3
Order By: Relevance
“…It indicates that the characteristics of the sample size do not significantly lead to heterogeneity in the effect sizes of the whole studies in this meta-analysis study. This result was similar to the previous MA study that the sample size characteristics did not cause the heterogeneity of the effect size of the studies conducted in the meta-analysis process (Demirel & Dağyar, 2016;Suparman et al, 2021;Yunita et al, 2020;Paloloang et al, 2020).…”
Section: B Analysis Of the Study Characteristicssupporting
confidence: 90%
“…It indicates that the characteristics of the sample size do not significantly lead to heterogeneity in the effect sizes of the whole studies in this meta-analysis study. This result was similar to the previous MA study that the sample size characteristics did not cause the heterogeneity of the effect size of the studies conducted in the meta-analysis process (Demirel & Dağyar, 2016;Suparman et al, 2021;Yunita et al, 2020;Paloloang et al, 2020).…”
Section: B Analysis Of the Study Characteristicssupporting
confidence: 90%
“…This means that the sample size does not change the effect size. This study is consistent with previous research which found that the study sample size did not change the effect size of the study [30][33][35]- [36]. However, this is different from the results of other studies which found differences in the effectiveness of treatment in learning based on sample size [21]- [22] [37].…”
Section: Figure 2 Funnel Plot Effect Size Distributionsupporting
confidence: 86%
“…This research has followed that stage. This stage has been implemented by other researchers in the field of education, for example (Turgut & Turgut, 2018;Paloloang et al, 2020;Suparman et al, 2021;Susanti et al, 2020;Yunita et al, 2020;Suparman, Tamur, et al, 2021;Tamur, Kusumah, et al, 2021;Sari et al, 2021). This research has also followed these stages which are detailed as follows:…”
Section: Methodsmentioning
confidence: 99%